A longitudinal study of electronic cigarette use and onset of conventional cigarette smoking and marijuana use among Mexican adolescents. (1st November 2017) - Lozano, Paula; Barrientos-Gutierrez, Inti; Arillo-Santillan, Edna; Morello, Paola; Mejia, Raul; Sargent, James D.; Thrasher, James F.
Highlights: Early adolescents, who have tried e-cigarettes, but not cigarettes, were more likely to try conventional cigarettes 20 months later. Dual trial of conventional cigarettes and e-cigarettes at baseline was associated with marijuana use at follow-up. Trial of only e-cigarettes at baseline was not independently associated with marijuana use at follow-up. Abstract: Purpose: This study evaluated whether e-cigarette trial among Mexican adolescents increased the likelihood of trial and use of conventional cigarettes or marijuana use at follow-up. Method: A school-based longitudinal survey was conducted in 60 public middle schools from the three largest cities in Mexico. Students (12–13 years old) were surveyed in 2015 and followed up 20 months later (n = 6574). Generalized estimating equations models were used to evaluate the association between e-cigarette trial at baseline and conventional cigarettes smoking and marijuana use at follow-up. Result: Adolescents who had tried e-cigarettes (but not cigarettes) at baseline were more likely to have tried conventional cigarettes at followup compared to adolescents who had tried neither e-cigarettes nor cigarettes (43% vs. 24%, respectively; RR 1.41, 95% CI 1.18-1.70). We also found that adolescents who had tried both conventional cigarettes and e-cigarettes at baseline were more likely to have tried marijuana at follow-up compared to adolescents who had tried neither tobacco product (20% vs. 4%, respectively; RR 2.67, 95% CI 1.78–4.02). Trial of only e-cigarettes was not independently associated with marijuana use at followup. Conclusions: Adolescents who had tried e-cigarettes were more likely to have tried conventional cigarettes and marijuana 20 months later. Although e-cigarettes have been banned in Mexico, it is likely that additional policies and public health campaigns are needed to reduce adolescent use of e-cigarettes and its consequences.